(untitled) (Panacea Journal of Medical Sciences, 2022)
Introduction: Nowadays with increasing use of social media platforms for each and everything, there is an increasing trend for use of whatsapp based consultation for many diseases. But what’s app base impression has many limitations and may result in error in diagnosis. Objective: To compare Whatsapp based visual impression versus actual impression in patients of common skin disorders. Materials and Methods: In this cross-sectional comparative study held at Department of Dermatology of tertiary care hospital and referral centre in central India, 316 patients of common skin disorders attending Dermatology department were enrolled. Photographs of skin lesions in a patient suffering from skin disorders in pre-determined categories were taken and sent to by 2 independent expert dermatologists by Whatsapp and their impression was recorded. Later same patients were independently evaluated by same investigators by actual clinical examination. It was studied whether both evaluations were matched or not. Results: At the end of study overall, 69% patients’ photographic and clinical impression was matched. Among different groups of disorders, like fungal, bacterial, viral, pigmentary groups, average diagnosis matched in 51% to 80% cases. Highest percentage of diagnosis matched in pigmentary type of disorders at 80% and lowest percentage of diagnosis matched was 51% for papulosquamous disorders. Conclusion : Whatsapp consultation is frequently sought by patients suffering from various dermatological problems but it’s not accurate and not 100 % reliable. So clinical evaluation always has an upper hand over an impression made over a photo.